Professores de inglês em formação: (re)significações sobre inclusão de alunos com necessidades educacionais específicas em institutos de idiomas - Nazzari, Karina Rocha [UNIFESP] (2020)
This research aims at investigating how English language teachers in a language institute understand and define the concept of students with specific educational needs (SENs) as well as the ways in which these professionals use their repertoire to offer (or not) inclusive practices in their classrooms. To do so, teachers who participated in this study took part in an in-service course that provided them with opportunities to build knowledge through reflection upon practice (SCHÖN, 1983; WALLACE, 1991; SMYTH, 1992; LIBERALI [2010] 2015). Different activities and resources were discussed so as to help participants plan and adapt activities for their students with specific educational needs (SENs), and this experience is likely to have contributed to the built of teacher’s autonomy. Despite having our Brazilian Inclusion Act (LBI 13,146), it is possible to identify that there is a lack of specific guidance towards the registration and welcoming of SEN learners in language institutes. However, it is of utmost importance that we consider ways of including these learners. Once we get this process started, teachers, SEN learners, typical learners and the language institute staff as a whole will profit from the new learning opportunities that will be promoted by the interaction of all these parts. This research is inserted in the Critical Research Paradigm (FREITAS, 2003) and uses the Critical Collaborative Research (PCcol) (MAGALHÃES, 1990 - 2020) as a methodological basis for its development. The data collected for analysis comes not only from the participants’ interactions throughout the aforementioned in-service course, which was based on Vygotsky ([1997] 2012), but also from reflective sessions (MAGALHÃES, 2006c) with two of the participants. The results show that: (i) the senses in relation to the understanding and the definition of students with SENs seemed to have encompassed a more historical – cultural perspective; (ii) teachers managed to have started building on a collective repertoire with ideas for sharing inclusive practices and (iii) some (re)signification of the teaching practice of participants involved in the research contributed to a more independent and confident teaching performance when working with other students with SENs.